Accessing News in the Digital Era : The Case of Sarawak, Malaysia - Collin, Jerome; Ting, Su Hie; Ahmad Junaidi, Ahmad Hadzmy; Humaira, Raslie (Asian Scholars Network (ASNet), 2023)
Recent trends show that people around the world are increasingly accessing news via mobile devices and digital platforms such as search engines and social media. The study examined whether such trends were escalating in the contexts where a large number of people continued to access news from traditional media sources such as TV, news, and print. A survey of 512 respondents living in Sarawak, Malaysia was conducted (33.8% rural, 10% suburban, and 56.2% urban). The results showed that the mobile gadgets most commonly used to access news are smartphones (49%) and 29.5% of respondents used both smartphones and laptop computers to read the news. The streaming device most frequently used to get news was Chromecast with Google TV. A majority of the respondents read online newspapers but they mostly read free news. Only 21.7% subscribed to online news portals. A comparison showed that online newspaper was gaining popularity over printed newspapers, and the use of live news streaming, news video, and podcast was on the rise. The study revealed that 19.3% did not use any gadgets to read the news, and they relied on traditional forms such as TV, printed newspapers, and radio. The most popular TV news channels for the Sarawakians were TV3 Media Prima and the newly established TV Sarawak. Among pay TV, Astro was popular. The study showed the appeal of mainstream news outlets to satisfy the news needs of Sarawakian viewers for updates on daily news, local news, and breaking news in the digital era.